Analyzing aesthetic values in Stella Jang’s "Villain" lyrics - Agung Ridho Widhiatmoko; Khoridatun Laila Al Ayuni (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2022)
K-pop is a generic label which is currently the main strength of South Korea whose culture has spread to almost all countries in the world both in the fields of fashion, culinary, entertainment and even in the field of music. K-pop music can be very popular not only because of the hype music, but they also present a fun dance with the visuals of the idols which are more attractive and much enjoyed by consumers. However, not a few consumers are concerned with and pay more attention to music videos and interesting lyrics, which are a benchmark for how total K-pop is in the music industry. This study analyzes the music and lyrics of the song Villain by Stella Jang, a solo singer from South Korea as one of the songs that emphasizes interesting meaning and content.